Rewards, Workload, Work Stress, and Hospital Employee Performance: A Systematic Review - Fitriawati, Julin Dwi; Wardani, Ratna; Prasetyo, Joko; Indasah, Indasah; Wahyuningsih, Atik Setiawan (Lembaga Chakra Brahmanda Lentera (Chakra Brahmanda Lentera Institute) [CANDLE], 2026)
Background: Hospital employees operate in complex work environments where organizational rewards, workload, and work stress may influence job performance and ultimately affect healthcare quality and patient safety. Although these factors have been widely investigated, the evidence remains fragmented and context-specific. This systematic review synthesizes current evidence on the relationships between rewards, workload, work stress, and hospital employee performance. Methods: A systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were performed in PubMed, Scopus, and Google Scholar using predefined keywords related to rewards, workload, work stress, employee performance, and hospitals. Quantitative studies involving hospital employees that examined at least one of the three organizational factors and reported employee performance outcomes were included. Twenty-six studies met the eligibility criteria and were narratively synthesized. Result: All included studies employed cross-sectional designs and were conducted in Indonesia, with nurses representing the predominant study population. The evidence consistently indicated that higher workload and work stress were associated with poorer employee performance. Most studies also reported that rewards, particularly financial compensation and incentive systems, were positively associated with employee performance through enhanced motivation and job satisfaction. However, one study found no significant association. Variability in reward-related findings appeared to reflect differences in organizational context and reward system implementation. Conclusion: Rewards, workload, and work stress are key organizational factors associated with hospital employee performance in Indonesia. Optimizing workload distribution, implementing fair and transparent reward systems, and strengthening workplace stress management may contribute to improved workforce performance and service quality. Given that all included studies were conducted in Indonesia and used cross-sectional designs, further longitudinal and multinational research is needed to strengthen the evidence base and improve the generalizability of these findings.